Enhancing Reading Comprehension Skills of Class VIII Students through Short Story Implementation: A Case Study at Karya Sejahtera Padangsidimpuan Madrasah Tsanawiyah Education Foundation - Harahap, Netti Herawati; Sibuea, Erni Rawati; Harahap, Rosni (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
This research investigates the effectiveness of using short stories to improve reading comprehension skills among Class VIII students at the Karya Sejahtera Padangsidimpuan Madrasah Tsanawiyah Education Foundation. The study involved 30 randomly selected students, and data was collected through both literature review and field research. A written test was administered as the data collection instrument. Statistical analysis was conducted to analyze the results. The findings revealed a significant increase in students' reading comprehension skills after the implementation of short stories. The average scores improved from 53 in the pre-test to 60 in posttest 1 and further to 90.87 in posttest 2. The percentage increase between pre-test and posttest 1 was 23.33%, while between pre-test and post-test 2 it was 70.3%. These results suggest that incorporating short stories in teaching can effectively enhance students' reading comprehension abilities. This research contributes to the body of knowledge on innovative teaching methods and their impact on educational outcomes, particularly in the context of Madrasah Tsanawiyah education.